Characterization of oral polymorphonuclear neutrophils in periodontitis patients: a case-control study - Elena A. Nicu; Patrick Rijkschroeff; Eva Wartewig; Kamran Nazmi; Bruno G. Loos (BMC, 2018)
Abstract Background Maintaining oral health is a continuous and dynamic process that also involves the immune system. Polymorphonuclear neutrophils (PMNs) migrate from blood circulation and become apparent in the oral fluid. Controversies exist regarding the specific role of the oral PMNs (oPMNs) in the presence of chronic oral inflammation, such as periodontitis. In this study we characterized cell counts, activation status, apoptosis, and reactive oxygen species (ROS) generation by oPMNs and circulatory (cPMNs), and the salivary protease activity, in subjects with and without periodontitis. Methods Venous blood and oral rinse samples were obtained from 19 patients with untreated periodontitis and 16 control subjects for PMN isolation. Apoptosis and expression of cell activation markers CD11b, CD63, and CD66b were analyzed using flow cytometry. Constitutive ROS generation was detected using dihydrorhodamine123. Additionally, ROS production in response to stimulation was evaluated in samples incubated with 10 μM phorbol myristate acetate (PMA) or Fusobacterium nucleatum. Total protease activity was measured using substrate PEK-054. Results Periodontitis patients presented with over 4 times higher oPMN counts compared to controls (p = 0.007), which was a predictor for the total protease activity (r 2  = 0.399, P = 0.007). More oPMNs were apoptotic in periodontitis patients compared to the controls (P = 0.004). All three activation markers were more expressed on the oPMNs compared to the cPMNs (p < 0.05), and a higher expression of CD11b on the oPMNs from periodontitis patients was observed compared to the control subjects (P = 0.024). Constitutive ROS production per oPMN was higher compared to the cPMN (P < 0.001). Additional analysis showed that the oPMNs retained their ability to respond to stimulation, with no apparent differences between the periodontitis and control subjects. Conclusions Higher numbers of oral PMNs, being more apoptotic and having increased levels of degranulation markers were found in periodontitis compared to periodontal health. However, since the oPMNs in periodontitis were responsive to ex vivo stimulation, we conclude that the oPMNs are active in the oral ecosystem. It is currently unknown whether the oPMN counts, which correlated with the detected protease levels, are detrimental in the long term for the oral mucosa integrity. Trial registration This study was retrospectively registered at the ISRCTN registry (trial ID ISRCTN15252886). Registration date August 11, 2017.